2020
DOI: 10.1111/jfb.14266
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic and immune responses of Chinook salmon (Oncorhynchus tshawytscha) smolts to a short‐term poly (I:C) challenge

Abstract: Polyinosinic:polycytidylic acid [poly (I:C)] was administered in vivo to Chinook salmon (Oncorhynchus tshawytscha) post‐smolts to determine the immune responses on haematological and cellular functional parameters, including spleen (SP), head kidney (HK) and red blood cell (RBC) cytokine expression, as well as serum metabolomics. Poly (I:C) in vivo (24 h exposure) did not affect fish haematological parameters, leucocyte phagocytic activity and phagocytic index, reactive oxygen species and nitric oxide producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 106 publications
(186 reference statements)
1
22
0
Order By: Relevance
“…Furthermore, liver levels of NEAA, 1‐aminocyclopropane‐1‐carboxylic acid and serine were co‐influenced by age and sex. The authors recently detected 1‐aminocyclopropane‐1‐carboxylic acid in fish serum (Lulijwa et al ., 2020). Its physiological importance currently remains unresolved in fish.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, liver levels of NEAA, 1‐aminocyclopropane‐1‐carboxylic acid and serine were co‐influenced by age and sex. The authors recently detected 1‐aminocyclopropane‐1‐carboxylic acid in fish serum (Lulijwa et al ., 2020). Its physiological importance currently remains unresolved in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Slide smears were prepared using 10 μl of fresh plain blood following the protocol of previous work (Lulijwa et al ., 2020). Slides were air‐dried overnight, fixed with methanol and stained with Giemsa (51,811,826, Sigma‐Aldrich, Auckland, New Zealand).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TANK expression pattern result in turbot revealed high expression level in liver followed by kidney; however, no similar work has been yet carried out which need further information to compare the tissue-specific expression of TANK in teleosts. The expression pattern of TBK1 gene in turbot was similar to that in Dicentrarchus labrax in gonad and brain (Valero et al, 2015), followed by Larimichthys crocea in brain, gills, heart and intestine (Zhang et al, 2015) with little In several previous and recent studies, it is evidently reported that there is an involvement of the fish PRRs genes under viral infection and induction conditions such as poly (I:C) and TRBIV (Andresen et al, 2020;Go et al, 2016;Li et al, 2020;Lü et al, 2005;Lulijwa et al, 2020;Su et al, 2011;Xiao et al, 2011). immunology (Fortier et al, 2004).…”
Section: Discussionmentioning
confidence: 59%